2002
DOI: 10.1023/a:1021345724248
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Use Efficiency, Chlorophyll Fluorescence, and Reflectance Indices Associated with Ontogenic Changes in Water-Limited Chenopodium quinoa Leaves

Abstract: Net photosynthetic rate, radiation use efficiency, chlorophyll (Chl) fluorescence, photochemical reflectance index (PRI), and leaf water potential were measured during a 25-<1 period of progressive water deficit in quinoa plants grown in a glasshouse in order to examine effects of water stress and ontogeny. All physiological parameters except Fv/F m were sensitive to water stress. Ontogenic variations did not exist in Fv/F m and leaf water potential, and were moderate to high in the other parameters. The compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…These findings are similar to studies focused on water stress, which have shown positive relationships between PRI and fluorescence (Peñuelas et al 1998;Winkel et al 2002). During the same 2007 field season, Naumann et al (2008b) showed that M. cerifera experienced a drought response, as seen in decreases in stomatal conductance, photosynthesis, and RWC relative to earlier in the season.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are similar to studies focused on water stress, which have shown positive relationships between PRI and fluorescence (Peñuelas et al 1998;Winkel et al 2002). During the same 2007 field season, Naumann et al (2008b) showed that M. cerifera experienced a drought response, as seen in decreases in stomatal conductance, photosynthesis, and RWC relative to earlier in the season.…”
Section: Discussionsupporting
confidence: 84%
“…Photochemical reflectance index, the PRI, has been demonstrated to be related to light use efficiency (Winkel et al 2002). For all species but M. indica, PRI values were highest in mature leaves but lowest in juvenile or senescent ones.…”
Section: Spectral Reflectancementioning
confidence: 99%
“…R 705 ) (Gitelson and Merzlyak 1994); Structuralindependent pigment index (SIPI) as (R 800 -R 445 )/ (R 800 -R 680 ) (Peñuelas and Filella 1998); Anthocyanin reflectance index (ARI) as 1/R 550 -1/R 700 (Gitelson et al 2003); and Photochemical reflectance index (PRI) as (R 530 -R 570 )/(R 530 ? R 570 ) (Winkel et al 2002). Where R is reflectance, the subscript number of R represents a specific wavelength.…”
Section: Spectral Reflectance Of Leaf Upper Surfacementioning
confidence: 99%
“…antheraxanthin or lower photosynthetic capacity were not associated with higher level of F v /F m in dry summer. It was also pointed out that PRI (Winkel et al 2002) or both photosynthesis and PRI (Richardson et al 2004) was more sensitive than F v /F m to water deficits. For the engagement of zeaxanthin ?…”
Section: Resultsmentioning
confidence: 99%
“…The relationships between PRI and photochemical efficiency and/or between PRI and net CO 2 uptake have been examined in many cases involving different seasons (Stylinski et al 2002;Nakaji et al 2006;Weng et al 2006a, b), elevations (Richardson et al 2001(Richardson et al , 2003Richardson and Berlyn 2002) and fertilizer regimes (Gamon et al 1992;Peñuelas et al 1994Peñuelas et al , 1995Gamon et al 2001). In addition, some reports also pointed out that PRI (Winkel et al 2002) or both photosynthesis and PRI (Richardson et al 2004) was more sensitive than F v /F m to water deficit.…”
Section: Introductionmentioning
confidence: 99%